The Efficiency-Based Drug Supply Strategy at Mardi Waluyo Hospital, Metro Lampung - Sekarjati, Irene; Purwadhi, Purwadhi; Mulyani, Kahar (International Journal on Advanced Science, Education, and Religion, 2025)
The Drug inventory management in hospitals is a crucial aspect of operational efficiency and healthcare service delivery. Ineffective inventory management can lead to waste, stock shortages, and financial losses for hospitals. This study aims to analyze managerial strategies in drug inventory management at Mardi Waluyo Metro Lampung Hospital to enhance the efficiency and effectiveness of drug distribution and utilization. The research employs a qualitative approach with in-depth interview techniques involving the head of the pharmacy installation and pharmaceutical logistics procurement staff. The analysis covers the processes of drug selection, demand planning, procurement, receipt, storage, distribution, disposal, and adjustment. The findings indicate several challenges in drug inventory management, including discrepancies between stock data and physical stock, a high number of expired drugs, and a lack of control systems for drug usage across hospital service units. To address these issues, this study recommends implementing a technology-based management system to improve stock recording accuracy, enforcing strict First In First Out (FIFO) and First Expired First Out (FEFO) methods, and optimizing policies for the disposal of unused drugs. The implementation of these strategies is expected to enhance hospital operational efficiency and reduce potential waste in drug inventory management